2014
DOI: 10.1176/appi.ajp.2014.13121571
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Maternal and Paternal PTSD on Epigenetic Regulation of the Glucocorticoid Receptor Gene in Holocaust Survivor Offspring

Abstract: Objective Differential effects of maternal and paternal PTSD have been observed in adult offspring of Holocaust survivors in both glucocorticoid receptor sensitivity and vulnerability to psychiatric disorder. The current study examined the relative influences of maternal and paternal PTSD on DNA methylation of the exon 1F promoter of the glucocorticoid receptor gene (NR3C1) in peripheral blood mononuclear cells (PBMCs), and its relationship to glucocorticoid receptor sensitivity, in Holocaust offspring. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
262
2
13

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 416 publications
(283 citation statements)
references
References 40 publications
6
262
2
13
Order By: Relevance
“…Methylation of gene promoter regions typically inhibits gene transcription (Klose and Bird, 2006). Indeed, Holocaust survivor offspring with paternal PTSD exhibited higher NR3C1 promoter methylation, whereas offspring with both maternal and paternal PTSD exhibited lower NR3C1 methylation (Yehuda et al, 2014).…”
Section: Epigeneticsmentioning
confidence: 99%
“…Methylation of gene promoter regions typically inhibits gene transcription (Klose and Bird, 2006). Indeed, Holocaust survivor offspring with paternal PTSD exhibited higher NR3C1 promoter methylation, whereas offspring with both maternal and paternal PTSD exhibited lower NR3C1 methylation (Yehuda et al, 2014).…”
Section: Epigeneticsmentioning
confidence: 99%
“…Notably, perturbations such as parental stress, malnutrition, infection, or advanced age have been associated with an increased incidence of neurodevelopmental disease in offspring (1), and alterations in their hypothalamic-pituitary-adrenal (HPA) stress axis response may be central to increased disease predisposition (2,3). Studies in diverse animal models have demonstrated similar outcomes, particularly that of offspring HPA axis dysregulation, following either maternal or paternal stress exposure (4-7); yet mechanisms by which parental lifetime stress experience modify offspring development and adult phenotypes remain unclear.…”
mentioning
confidence: 99%
“…As one pathway is overloaded from chronic exposure to addictive substances (including behavior) or extreme stress, the other pathway will also become overloaded causing cumulative dysregulation in emotional, behavioral and cognitive domains that cause downstream effect on the ANS and epigenetic translation and intergenerational transfer due to dysregulation of these life-supporting systems. 72) An important question remains as to how intervention and treatment can repair and/or restore the aberrant pathways to normal functioning. Perhaps lessons can be learned from observing patients who are in active and long-term recovery from both CT and addiction, and have seemingly improved the function of RewP and RegP pathways.…”
Section: Commentarymentioning
confidence: 99%